PREVALENCE OF LOW BACK PAIN AND ITS ASSOCIATED FACTORS AMONG STAFF NURSE IN SELECTED HOSPITAL, CHENNAI - T. Deborah Mercy Bai; Dr. V. Hemavathy (The Bioscan, 2025)
Introduction: Low back pain (LBP) is a significant occupational health issue, particularly among nurses, who are frequently exposed to physical demands that predispose them to musculoskeletal disorders. Aim: The study aimed to assess the prevalence of low back pain and its associated factors among staff nurse in selected hospital, Chennai. Methodology: This cross-sectional descriptive study was conducted at Sri Balaji Medical College and Hospital, Chennai, from June to July 2024, to assess the prevalence of low back pain (LBP) and its associated factors among staff nurses. A total of 120 nurses were selected through convenience sampling. Inclusion criteria included registered nurses with at least six months of clinical experience who provided informed consent. Nurses on leave during data collection or working in non-clinical roles were excluded. Result: The study revealed that 61.7% of staff nurses experienced low back pain (LBP) in the past year, with 32.5% reporting symptoms in the past week. Among them, 23.3% had recurrent episodes, and 17.5% took medical leave. Most reported moderate pain and 1–4 weeks of duration, with over half indicating work interference. Significant associations were found between LBP and years of experience (p = 0.003), frequent patient lifting (p = 0.021), and lack of ergonomic training (p = 0.004), highlighting key occupational risk factors. Conclusion: The study concluded that low back pain is highly prevalent among staff nurses and is significantly associated with factors like frequent patient lifting, years of experience, and lack of ergonomic training.